Groundwater quality mapping of an alluvial aquifer, Eshtehard, Iran - Khodapanah, Leila; Sulaiman, Wan Nor Azmin (Universiti Putra Malaysia Press, 2011)
Eshtehard aquifer located in southwest of Tehran province, Iran, provides a large amount of water requirement for inhabitants of Eshtehard district. Monitoring and analyzing of groundwater quality are important for protecting groundwater as sustainable water resource. One of the most advanced techniques for groundwater quality interpolation and mapping is geostatistics methods. The purposes of this study are (1) to investigate major ions concentration and their relative abundance to provide an overview of present groundwater chemistry and (2) to map the groundwater quality in the study area using geostatistics techniques. In this investigation, ArcGIS 9.2 was used for predicting spatial distribution of some groundwater characteristics such as: Chloride, Sulfate, pH, and Conductivity. These methods are applied for data from 44 wells within the study area. The final maps show that the south parts of the Eshtehard aquifer have suitable groundwater quality for human consumption and in general, the groundwater quality degrades south to north and west to east of the Eshtehard plain along the groundwater flow path.